Comparison of Augmented Bone versus Pristine Bone by Monitoring Peri-implant Bone Level Changes. - Huang, Hsiang-yun. (2017)
Abstract: Background Bone augmentation, which also named as guided bone regeneration (GBR) procedure, is utilized in contemporary dentistry on implant related sites to get sufficient bone volume for implant placement to have better functional and esthetic outcome. The purpose of the present study was to compare the peri-implant bone levels changes of implants placed in augmented bone versus in pristine bone. Materials and Methods Twenty-nine submerged implants (11 from test group and 18 from control group) were placed in 26 human subjects. The test implants were placed in previously augmented ridge, whereas the control implants were placed in pristine alveolar ridge. All implants were placed in mandibular posterior arch. Customized radiographic stents were used to obtain standardized radiographs at the time of implant placement and stage II procedure. The mesial and distal peri-implant bone levels were measured from standardized radiographs by utilizing image-analyzing software. At the time of stage II procedure, the width of keratinized mucosa (wKM), thickness of soft tissue (ST) over the implant site and the classification of early implant exposure (eIE) were also recorded. Significantly statistical differences in mesial, distal and mean peri-implant bone level loss between test and control group were evaluated by using the mixed effects model with and without adjusting the potential cofounders (wKM, ST and eIE) Results The Mean peri-implant bone loss (ΔBL) was 0.74 ± 0.74 mm (Mean ± SD) for the test group and 0.25 ± 0.55 mm for the control group (P= 0.0007). The mesial peri-implant bone loss (ΔMBL) was 0.81 ± 0.85 mm for the test group and 0.30 ± 0.72 mm for the control group (P=0.0092). The distal peri-implant bone loss (ΔDBL) was 0.67 ± 0.77 mm for the test group and 0.20 ± 0.49 mm for the control group (P=0.0038). There was a statistically significant difference between test and control group for mesial, distal and mean peri-implant bone loss with adjusting the potential confounders. Conclusions With the limitation of the study, more bone resorption during the submerged implant healing period was observed in the test group compared to control group. Augmented bone may not perform as the same characteristic of pristine bone during the implant therapy, which could be a significant factor on peri-implant bone stability. Further studies with long-term follow up are recommended.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Periodontology.; Advisor: Yong Hur.; Committee: James Hanley, Matthew Finkelman, and Yumi Ogata.; Keyword: Dentistry.